2018
DOI: 10.1667/rr14897.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decrease in KRT14 and TP53 mRNA Expression in the Buccal Mucosa of Patients Receiving Total-Body Irradiation for Allogeneic Stem Cell Transplantation

Abstract: The only curative treatment option for relapsed patients with acute myeloid leukemia (AML) is allogeneic stem cell transplantation. Depletion of hematopoietic stem cells and leukemic blast cells is achieved through the systemic administration of DNA damaging agents, including total-body irradiation (TBI) prior to transplantation. Since other tissues are radiosensitive, the identification of biomarkers could facilitate the management of additional toxicities. Buccal keratinocytes are readily accessible and coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our test for migration and proliferation capacities allows one to estimate the radioresistance. Cells may be used for personalized models to investigate radiation-induced damage and additional cellular features [30] , [31] . Studies on the clinical relevance are presently underway, which include a larger sample size and detailed evaluation of mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Our test for migration and proliferation capacities allows one to estimate the radioresistance. Cells may be used for personalized models to investigate radiation-induced damage and additional cellular features [30] , [31] . Studies on the clinical relevance are presently underway, which include a larger sample size and detailed evaluation of mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from sublethal total-body irradiation (TBI) is associated with multiple delayed effects, including acceleration of age-related markers of aging (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), reduction of stem cell populations in multiple organs (1,(3)(4)(5), tissue and organ failure (9-10) and carcinogenesis (11)(12). Previously reported studies have demonstrated reduction in proliferative capacity of explanted stromal cells from the marrow of TBI mice at 3 months postirradiation (12).…”
Section: Introductionmentioning
confidence: 99%